2022
DOI: 10.3389/fcvm.2022.850538
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiac Dysfunction Caused by Metabolic Alterations in Alzheimer's Disease

Abstract: A progressive defect in the energy generation pathway is implicated in multiple aging-related diseases, including cardiovascular conditions and Alzheimer's Disease (AD). However, evidence of the pathogenesis of cardiac dysfunction in AD and the associations between the two organ diseases need further elucidation. This study aims to characterize cellular defects resulting in decreased cardiac function in AD-model. 5XFAD mice, a strain expressing five mutations in human APP and PS1 that shows robust Aβ productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…10. In a line with our results, (Stakos et al 2020;Cermakova et al 2015;Yeung et al 2014;Fioranelli et al 2018;Murphy et al 2022;Ewid et al 2020;Zhu et al 2022;Shen et al 2015) indicated that elevated Aβ serum level may be found to be associated with severe hypoxia, Fig. 8 Illustration of histopathological examination of cardiac tissues among subjected groups.…”
Section: Discussionsupporting
confidence: 90%
“…10. In a line with our results, (Stakos et al 2020;Cermakova et al 2015;Yeung et al 2014;Fioranelli et al 2018;Murphy et al 2022;Ewid et al 2020;Zhu et al 2022;Shen et al 2015) indicated that elevated Aβ serum level may be found to be associated with severe hypoxia, Fig. 8 Illustration of histopathological examination of cardiac tissues among subjected groups.…”
Section: Discussionsupporting
confidence: 90%
“…The pulmonary vein contains abundant amyloid peptides and directly influences atrial remodeling as a major substrate of AF [ 35 ]. Moreover, cardiac dysfunction of AD model mice and cytotoxicity of Aβ to cardiomyocytes have been reported [ 24 , 36 , 37 ]. Our study and others have reported that mitochondrial oxidative stress plays a pivotal role in the pathogenesis of both AD and AF [ 20 , 38 ], which could be attributed to Ca 2+ overload, ROS generation and energy deprivation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The production of cardiac mitochondrial reactive oxygen species (ROS) was determined in both human LV tissues and mouse LV tissues using our previously described protocol [ 20 ]. Briefly, this was evaluated via wheat germ agglutinin (WGA) and MitoSOX Red staining.…”
Section: Methodsmentioning
confidence: 99%